Auditory risk of exposure to ballistic N-waves from bullets. (25th January 2019) - Flamme, Gregory A.; Murphy, William J.
Abstract: Objective: Assessment of the auditory risk associated with sound from ballistic N-waves produced by a rifle bullet. Design: Acoustical recordings of ballistic N-waves passing through a microphone array at 6.4 metres down range were analysed to determine (a) the trajectory of the bullet, (b) the distance between the trajectory and each microphone (less than 1.3 m), and (c) the numbers of permissible exposures according to both damage-risk criteria for impulsive noise in the current U.S. military standard (MIL-STD-1474E). Study Sample: The gun was an AR-15 style semiautomatic rifle configured to fire a 0.50 calibre Beowulf 00AE cartridge. Four sample shots were recorded for each of four microphone spacing conditions and five kinds of ammunition (80 shots in total). Results: The ballistic N-waves recorded in this study would constitute a significant auditory risk to unprotected listeners at all distances sampled. The numbers of permissible exposures decreased as the distance to the bullet trajectory decreased, decreased with increased bullet length, and departed from linear increases as the bullet velocity increased. Conclusions: Unprotected exposure to a ballistic N-wave from a supersonic 0.50 calibre bullet presents a significant risk to hearing at distances of 6.4 metres down range and through trajectories within 1.2 metres of an ear.